STUDIES ON THE LEUCOCYTIC PICTURE IN BRUCELLOSIS - RUIZ CASTANEDA, MAXIMILIANO; GUERRERO, HG (HOSPITAL GENERAL, LABORATORIO DEL TIFO, CD. MEXICO, DF, MEX, 1975)
An histologic study of the brain in human cerebral cysticercosis with few parasites shows no lesions other than the inflammatory reaction localized around the parasite In cases of multiple cysticercosis there is an intense diffuse meningovascular alterat
J INFEC DIS
Keywords: STUDIES, LEUCOCYTIC, PICTURE, BRUCELLOSIS; CIENCIAS MEDICAS; MEDICINA INTERNA; ENFERMEDADES INFECCIOSAS